2023
DOI: 10.1038/s41598-023-32584-7
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of probiotic on nonalcoholic fatty liver disease and lipolytic gene expression in rabbits

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a condition that affects about 24% of people worldwide. Increased liver fat, inflammation, and, in the most severe cases, cell death are all characteristics of NAFLD. However, NAFLD pathogenesis and therapy are still not clear enough. Thus, this study aimed to determine the effect of a high-cholesterol diet (HCD) inducing NAFLD on lipolytic gene expression, liver function, lipid profile, and antioxidant enzymes in rabbits and the modulatory effects of probiotic Lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…In the study of Crommen and Sherf-Dagan et al, the bacterium types included Lactobacillus and Bifidobacterium . It was reported Lactobacillus and Bifidobacterium can protect against NAFLD, and restored liver functions to normal levels [ 46 , 47 ]. This suggested that probiotics may be used as an adjunct therapy for patients with morbid obesity undergoing bariatric surgery so to help in alleviating liver damage in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Crommen and Sherf-Dagan et al, the bacterium types included Lactobacillus and Bifidobacterium . It was reported Lactobacillus and Bifidobacterium can protect against NAFLD, and restored liver functions to normal levels [ 46 , 47 ]. This suggested that probiotics may be used as an adjunct therapy for patients with morbid obesity undergoing bariatric surgery so to help in alleviating liver damage in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Altered intestinal flora can affect lipid metabolism in various mechanisms. In the study of Aziz et al, it was reported that Lactobacillus restored lipolytic gene expression [ 46 ]. Lactobacillus and Bifidobacterium can improve the short-chain fatty acids (SCFAs) which had been shown to improve lipid signaling [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%